Comparative genomics of carbapenem-resistant Pseudomonas aeruginosa strains sequence type 3151 isolated from two major hospitals in Hanoi, Vietnam - Quang Huy, Nguyen; Bich Ngoc, Do; Thanh Tam, Tran Thi; Thu Hang, Le Thi; Nhung, Doan Thi; Bañuls, Anne-Laure (Vietnam Journal of Biotechnology, 2023)
Carbapenem-resistant Pseudomonas aeruginosa belongs to the critical species of global priority pathogens, nevertheless, molecular mechanisms of such resistance in low- and middle-income countries are limited. In this context, we conducted a comparative genomic analysis between two clinical carbapenem-resistant P. aeruginosa strains VD641 and XP646 isolated from hospitals in Hanoi, Vietnam. The phenotypic-resistant profile revealed that both strains were resistant to at least 26 drugs belonging to 6 different antibiotic classes, and therefore they were identified as extensively drug-resistant bacteria. The chromosomal genome of strain VD641 was 7.1 Mb with GC a content of 65%, while the genome of XP646 consisted of an approximately 7.3 Mb with a GC content of 64.8%.  The two strains belong to sequence type 3151 (ST3151). Genomic comparative analysis revealed that VD641 possessed higher numbers of antimicrobial resistance genes compared to XP646 (35 and 26 genes, respectively). This data was in accordance with their antibiotic-susceptibility profiles. Notably, the strain VD641 acquired a multidrug-resistant gene region with 223 kb in length carrying 11 antibiotic-resistant genes. Strains VD641 and XP646 acquired a blaIMP-15 and blaKPC-2 carbapenem-resistant gene, respectively. Analysis of virulent protein-protein interaction networks revealed six gene clusters involving the pathogenicity of the ST3151. Finally, four plasmids found in P. aeruginosa XP646 (n=1) and VD641 (n=3) carried different ARGs genes. The draft genomes and plasmid sequences of P. aeruginosa VD641 and XP646 were submitted to GenBank under BioSample accessions SAMN39268202 and SAMN39268203, respectively. The findings in our study underline that genomic surveillance is essential for management of carbapenem resistance emergence in healthcare setting in Vietnam.